Pengaruh Electronic Word Of Mouth dan Brand Image terhadap Keputusan Pembelian Sunscreen Azarine (Survei pada pengguna aplikasi tiktok) - Prihadini, Diana; Krishantoro, Krishantoro; Nanda, Ilyas Fitra (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2023)
The objective of this study is to find out the Influence of Electronic Word Of Mouth and Brand Image To Sunscreen Azarine Buying Decision. This study used quantitative research method. The data was collected from questionnaire and literature. Population in this study is user of Sunscreen Azarine and follow tiktok account @Azarinecosmetic. Sampling Technique used Taro Yamane Formula. There are 100 samples. The data analysis used in this study is multiple linier regression analysis using a software of IBM Statistik version 26. Result of the study identified that Electronic Word Of Mouth partially not influence to Buying Decision is in the amount of 39,6% . Brand Image partially has influence in the amount of 61.4% to Buying Decision. Electronic Word Of Mouth and Brand Image simultaneously affected significantly to Buying Decision with value of 61,4% where 38,6% explained by other factors excluded from this study.